THE FORMATION OF VOTERS FROM FAMILY AND EDUCATIONAL CONTEXT - Augusto, Daniel Cirilo; da Silva, Márcia (European Scientific Journal, ESJ, 2014)
The objective of this work is analyzing the development of some places since people’s educational and family formation. Basing on family and school, for example, we explain into this research that electoral behavior is a voters’ probable evidence of reflexive aptitude about development of some places. Results demonstrate that index of educational level and revenue allows these voters think about political and ideological characteristics of some places where they are. We can say that these people are able to think about strategies to develop the place where they live. In general, we also observe that voters and partisan policy are far one to another and voters, a priori, do not consider that the participation in electoral actions is important. Discussions on this work start from this question: are there any elements responsible to formalize a connection between voters and partisan policy? Then this work tries to answer this question based on theoretical debates about the subject and exemplifying realities before studied.